Business Process Reengineering Menuju Proses Berdaya Saing Tinggi - Suhardi, Bambang (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2006)
Some people made a wrong concept about Business Process Reengineering (BPR). Some were misunderstanding about the BPR term. In other way, so many researches were introduced to describe a better definition about BPR. The thinking about concepts, causes, and effects of BPR will make a new perception about the term ofBPR itselfas a better methodology instead ofthe other Quality Management Methodology such as Total Quality Management (TQM). Just In Time (JIT), etc